On Some Forms of Closed Sets and Related Topics (European Journal of Pure and Applied Mathematics, 2023)
The purpose of the present article is to introduce the notion of (Λ, s)-closed sets. Especially, some properties of generalized (Λ, s)-closed sets are obtained. Several characterizations of some low separation axioms are given. Characterizations of (Λ, s)-extremally disconnected spaces are investigated. Furthermore, some characterizations of almost (Λ, s)-continuous functions are discussed.
Keywords: $(Λ,s)$-closed set; generalized $(Λ,s)$-closed set; $(Λ,s)$-$R_0$ space; almost $(Λ,s)$-continuous function